ANALISIS KEYAKINAN DIRI PASIEN DIABETES MELLITUS TIPE 2 DALAM PENGELOLAAN DIABETES MELLITUS - Alfeus Manuntung (Politeknik Kesehatan Kemenkes Mamuju, 2017)
Diabetes Mellitus Type 2 is the most common endocrine disease and the most common form of diabetes. DM Type 2 needs of medical care and self-management education to prevent acute complications and reduce the risk of long term complications. Patients with DM usually ignore or be unaware of characters DM. Self efficacy is an essential element for improving self-care behavior of patients with DM type 2. The objective of this study was to analyze the patient's self efficacy in the management of DM Type 2 at Puskesmas Panarung of Palangka Raya City with descriptive correlational research design using cross sectional approach. This research uses descriptive correlational design with cross sectional approach. The sampling technique in this research is to use sampling techniques nonprobability concecutive sampling. The data collection is done by measuring the level of self efficacy using a questionnaire. The statistical test used was descriptive test and Chi Square test. The results showed that there is no significant relationship between age and self efficacy of respondents, no significant correlation gender with self efficacy of respondents, no significant correlation level of education and self efficacy of respondents, there is no significant employment with self efficacy of respondents, there is no correlation significant income with self efficacy of respondents, and there is a significant relationship between long-suffering DM with self efficacy of respondents. The conclusion of this research are there is no relationship between age, gender, level of education, employment, and income with self efficacy, while long suffered from DM found a significant relationship with the self efficacy. However, further research with controlled randomized clinical study design and the large sample size needs to be done to develop nursing interventions with behavioral approaches in order to increase self efficacy and self-care behaviors that can reduce complications.